Dual (magnetic and pH) stimuli-reversible Pickering emulsions based on poly(2-(dimethylamino)ethyl methacrylate)-bonded Fe3O4 nanocomposites for oil recovery application. Issue 2 (April 2020) - Low, Liang Ee; Ooi, Chien Wei; Chan, Eng Seng; Ong, Boon Hoong; Tey, Beng Ti
Graphical abstract: Highlights: Fe3 O4 @PDMAEMA nanocomposite (PDMNC) was successfully produced. PDMNC-stabilized Pickering emulsion (PDMNC-PE) was pH- and magnetic- responsive. Reversible stability of PDMNC-PE under changes in pH and magnetic field lasted for at least 6 cycles. Oil can be recovered magnetically utilizing the stimuli-responsiveness of PDMNC-PE. Abstract: Stimuli-responsive Pickering emulsion system has received considerable scientific interests for myriad applications. In this contribution, nanocomposites (PDMNC) made of Fe3 O4 nanoparticle and poly[2-(dimethylamino)ethyl methacrylate] were prepared through a facile sonochemical in situ co-precipitation approach and were used in the preparation of Pickering emulsion system (PDMNC-PE). PDMNC-PE exhibited pH-responsive behavior and it was stable at pH ranging from 5 to 9. Upon magnetic exposure, PDMNC-PE underwent repeatable and rapid emulsification/demulsification triggered by a change in pH for at least six cycles. The stabilization/destabilization of PDMNC-PE was caused by the synergistic effect from magnetic force, surface hydrophobicity and zeta potential of PDMNC in response to pH, which resulted in the adsorption/desorption of PDMNC at the interface of the Pickering emulsions. The magnetic- and pH-reversible PDMNC-PE has a great potential for application in oil recovery.